Nursing management of treatment-related venous thromboembolism in patients with multiple myeloma - Yang, Bianhong; Liu, Chao; Lin, Zeyu; Geng, Chuanying; Zhang, Zhiyao (Frontiers in Medicine, 2023)
Abstract Objectives: Venous thromboembolism (VTE) is a common complication of newly diagnosed multiple myeloma (NDMM) patients This study aimed to analyze incidents and the risk factors of VTE in the era of thromboprophylaxis and propose corresponding nursing measures. Methods: A total of 1539 NDMM patients were retrospectively analyzed. All patients were assessed for VTE risk, given aspirin or low molecular weight heparin (LMWH) to prevent thrombosis, and given appropriate care based on the thrombosis risk assessment. The incidence of venous thromboembolism and related risk factors were analyzed. Results: All patients received at least 4 cycles of therapy containing immunomodulators (IMiDs) and/or proteasome inhibitors (PIs). Among them, 371 (24.1%) patients were assessed as the moderate risk of thrombosis group, who took aspirin 75mg daily for thrombosis prevention, and 1168 (76.9%) patients were assessed as a high-risk group, who took low molecular weight heparin 3000IU daily for thrombosis prevention, q12h. Lower extremity venous thromboembolism events occurred in 53 patients (3.4%), including 3 patients with concurrent pulmonary embolism. Multivariate analysis suggested that bed rest for more than 2 months and plasma cells ≥60% were independent factors associated with thrombosis. Conclusion: More effective risk assessment models to predict thrombosis are needed. In addition, the nurse on myeloma disease treatment of thrombosis in the process of cognition and management should be constantly learning and improving.